Symbolic Adoption of Livestock Based Technologies After Termination of NAIP - K.L.Dangi; Ramesh Kumar Damor (Indian Journal of Extension Education, 2013)
The National Agricultural Innovation Project (NAIP) was launched in the country during 2006. It has been focusing on innovations in agricultural technology. The objective was to address the poverty elevation and creating income generation avenues for disadvantaged people leading to livelihood and nutritional security. The consortium project worth ` 18.3 crore was given to MPUAT Udaipur, Rajasthan. Process evaluation of livestock based IFS interventions in terms of symbolic adoption behavior of tribals about Livestock based IFS was carried out in Dungarpur District of Rajasthan, India. Total 104 beneficiaries were interrogated and respondents were categorized into three groups of future possibilities of adoption level along with ranking of sub- interventions to be adopted in livestock. The results indicated that majority 95.19 per cent of tribals expressed moderate certainty for future adoption of livestock based IFS interventions followed by 4.81per cent of them reporting high certainty of future adoption of IFS interventions even after the termination of the project. No respondent was found under low certainty of adoption. Further, Improved farm implements, Artificial Insemination, Green fodder production, feeding pattern, Nirbhik breed of poultry, processing equipments and selling of products at the collection centers were the sub- aspects of Livestock based IFS for which the NAIP beneficiaries were certain for continuing the adoption after closing of the project. The results are encouraging and reflecting the positive impact of NAIP on tribal beneficiaries in Dungarpur district of Rajasthan state. Based on the findings, it is recommended that the NAIPfor livestock based IFS must be replicated elsewhere with the same interventions and the beneficiaries of the area be supported for sustaining the advocated interventions after its termination.